2015
DOI: 10.17795/nmsjournal29143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Self-Efficacy in Senior Nursing Students: A Mixed- Methods Study

Abstract: Background:Clinical education has a basic role in nursing education, and effective clinical training establishes a sense of clinical self-efficacy in senior nursing students. Self-efficacy is a key component for acting independently in the nursing profession.Objectives:This study was designed to outline senior nursing students’ views about clinical self-efficacy and to determine its level in nursing students.Patients and Methods:A mixed-methods approach, including a quantitative cross-sectional study and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 21 publications
1
35
1
9
Order By: Relevance
“…The regression analysis revealed a predictor model for perceived competence (PCNS), including both types of self‐efficacy, resilience, and academic level as predictors. These variables appear separately in other regression models reported by other authors (Abdal, Alavi, & Adib‐Hajbaghery, ; Bifftu, Dachew, Tadesse Tiruneh, Mekonnen Kelkay, & Bayu, ; Mohamadirizi et al, ). This finding highlights the importance of self‐efficacy and resilience throughout the nursing curriculum, as variables, which foster perceived competence among nursing students.…”
Section: Discussionmentioning
confidence: 58%
“…The regression analysis revealed a predictor model for perceived competence (PCNS), including both types of self‐efficacy, resilience, and academic level as predictors. These variables appear separately in other regression models reported by other authors (Abdal, Alavi, & Adib‐Hajbaghery, ; Bifftu, Dachew, Tadesse Tiruneh, Mekonnen Kelkay, & Bayu, ; Mohamadirizi et al, ). This finding highlights the importance of self‐efficacy and resilience throughout the nursing curriculum, as variables, which foster perceived competence among nursing students.…”
Section: Discussionmentioning
confidence: 58%
“…They include academic and clinical experience, effective feedback during their course of study, supervision by educators and a positive environment (Abdal et al . , Masoudi Alavi ). This study adds spirituality of nursing students to that list.…”
Section: Discussionmentioning
confidence: 99%
“…Also, much nursing research has suggested that self‐efficacy is an important element of job satisfaction and retention in the nursing profession (Abdal et al . , Van Waeyenberg et al . , Duggleby et al .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical self‐efficacy among students is a crucial component for acting independently in the nursing profession, where it can reflect the educational situation of the nursing faculties . Students with high self‐efficacy feel more competent, which is crucial to their clinical success.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have confirmed that students with higher self‐efficacy face low levels of stress . Abdal et al showed ways to improve self‐efficacy and the factors affecting it, such as the surrounding environment, nursing colleagues, and clinical instructors; they could influence the creation of clinical self‐efficacy in students.…”
Section: Introductionmentioning
confidence: 99%